People's Sovereignty in the Intertime Change of Members of The Indonesian Council of Representatives - Sikumbang, Yudhia Perdana (LAW FACULTY UNISSULA, 2023)
This journal discusses the role and implementation of the concept of people's sovereignty in the context of the intersection of members of the Indonesian People's Council of Representatives. (DPR-RI). The sovereignty of the people, as a fundamental principle in a democratic system, is the primary foundation in the process of the realization of the will of people through political representation. This journal specifically explores how people's sovereignty is reflected in the replacement mechanism of DPR-RI members over time. Through a legal and political analysis approach, the journal outlines the legal framework that regulates the process of replacement of members of the DPR-RI and identifies the factors that influence the successful implementation of people's sovereignty in that context. This research includes a study of the role of related institutions, such as political parties and the General Election Commission, inining integrity and representation in line with people's aspirations. The results of this study provide a deep understanding of the extent to which the sovereignty of the people is preserved and updated in the process of changing members of the DPR-RI over time. The implications of these findings can provide valuable insights for policy formulation, the development of democratic systems, and the strengthening of people's political participation in the Indonesian context